2006
DOI: 10.1029/2005wr004560
|View full text |Cite
|
Sign up to set email alerts
|

Beaver dams and overbank floods influence groundwater–surface water interactions of a Rocky Mountain riparian area

Abstract: [1] Overbank flooding is recognized by hydrologists as a key process that drives hydrogeomorphic and ecological dynamics in mountain valleys. Beaver create dams that some ecologists have assumed may also drive riparian hydrologic processes, but empirical evidence is lacking. We examined the influence of two in-channel beaver dams and a 10 year flood event on surface inundation, groundwater levels, and flow patterns in a broad alluvial valley during the summers of 2002-2005. We studied a 1.5 km reach of the fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
243
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 226 publications
(255 citation statements)
references
References 30 publications
10
243
2
Order By: Relevance
“…Many of these valley bottoms may be wetlands simply because beaver may be maintaining riparian water tables near or at the ground surface by creating larger-scale (valley sized) hyporheic flow paths. Such hydrological connectivity may persist throughout wet and dry periods as this study and others (e.g., Westbrook et al, 2006) have shown that beaver keep hydrological conditions relatively static.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of these valley bottoms may be wetlands simply because beaver may be maintaining riparian water tables near or at the ground surface by creating larger-scale (valley sized) hyporheic flow paths. Such hydrological connectivity may persist throughout wet and dry periods as this study and others (e.g., Westbrook et al, 2006) have shown that beaver keep hydrological conditions relatively static.…”
Section: Resultsmentioning
confidence: 99%
“…Depth to water in wells and piezometers was measured as per Westbrook et al (2006). Stream stage was measured along the outside casing of the A-series piezometers.…”
Section: Instrumentation and Data Collectionmentioning
confidence: 99%
“…Beaver dams similarly enhance overbank flow, floodplain deposition and organic matter retention, and maintain high water tables that support dense stands of willow (Salix spp.) and other riparian shrubs [30][31][32] . The unequal distribution throughout the river network of carbon stored in floodplain sediment and coarse wood suggests that resource management designed to facilitate carbon storage can be most effectively focused on the relatively small proportion of channel segments with unconfined valleys.…”
Section: Discussionmentioning
confidence: 99%
“…Peatlands are commonly initiated before beavers enter the system (Gorham et al, 2007); however, beaver activity can create water-level changes conducive to wetland formation (Westbrook et al, 2006). Once a peatland is established, beavers dig canals and help to create and maintain deep, open water by damming seepage (Westbrook et al, 2013).…”
Section: Role Of Beavers In the Pliocene High Arcticmentioning
confidence: 99%